Response of freshwater transport during typhoons with wave-induced mixing effects in the Pearl River Estuary, China. (5th September 2021) - Zhang, Heng; Hu, Suan; Cheng, Weicong; Zhu, Lei; Chen, Yuren; Liu, Jiahuan; Gong, Wenping; Li, Yineng; Li, Shaotian
Abstract: We examined the response of freshwater transport in the Pearl River Estuary (PRE) to typhoons in 2017 to investigate the effects of wave-induced mixing under extreme conditions using a 1D-3D coupled river-ocean model with a wave-induced mixing module. The results show that wave-induced mixing trapped more freshwater in coastal regions by narrowing the plume width and increasing the freshwater thickness. The freshwater volume in the coastal region increased by 10%–60% and the flushing time increased from 5–42 days to 10–50 days. The trapping effect of wave-induced mixing was modulated by alongshore wind, wave and river flow, and it was sensitive to the initial freshwater thickness before typhoon. Cross-shore and eastward freshwater transport was substantially altered during typhoons by wave-induced mixing, whereas westward freshwater transport exhibited only minor changes. It was found that wave-induced mixing caused a change in vertical/horizontal density gradient, and thereby altered the freshwater volume, ocean current and freshwater flux. The effects of wave-induced mixing on the plume structure and flushing time scale were further investigated by applying a salinity coordinate system. The results show that wave-induced mixing significantly increased/reduced the plume area and freshwater volume in the far field (26–32)/near field (19–26) during typhoons. As a consequence, the flushing time in the near field/far field was reduced/increased. Shorter flushing times inside the estuary and longer flushing times on the shelf induced by wave-induced mixing have important implications for the fate of nutrients, sediments, and other pollutants. This study highlights that wave-induced mixing effects are important in modulating freshwater transport and flushing time scales, which are of great significance in regional coastal management to protect the marine environment. Highlights: The PRE freshwater transport response to typhoons is categorized into three types. Wave-induced mixing substantially reduces/increases the cross-shore/upshelf freshwater transport during typhoons. Wave-induced mixing changes the freshwater volume more efficiently in the far field of the plume. Wave-induced mixing increases the freshwater flushing time by 10%–60%.